ANALISIS FAKTOR PRIORITAS MAHASISWA DALAM MEMILIH JURUSAN DENGAN FUZZY ANALITIC HIERARCHY PROCESS - Benny Sofyan Samosir; Wiwik Novitasari; Safran Efendi Pasaribu (Universitas Muhammadiyah Semarang, 2018)
University is the institution engaged in public service namely education services needs to identify the student candidates on education product, develops educational products and implements marketing activities to attract the attention of the student candidates. The purpose of this study is to determine priority consideration for students in choosing a study program at the College. The method used in this study is Fuzzy Analysis Hierarchy Process (FAHP), with the results of the study, the order's rank criteria factor (Study Program profile, Infrastructure, The Activity of study Program and Rules of Conduct), the rank order of the sub factor infrastructure criteria (Quality of College Building, Library, Sport Facilities, Laboratory), the order of sub-criteria rank factor of study Program profile ( lay out and Accreditation of study program, the length of the Study, Graduates Lecturer), a sequence of sub criteria ranking factors study program of activities (Seminar, Community Service, fieldtrip, Research), and the sequence of sub-criteria rank factor of the order of (Lectures, students number, Clothing, Leaves).